2020
DOI: 10.3389/fneur.2020.00640
|View full text |Cite
|
Sign up to set email alerts
|

A Contemporary Review of Neurological Sequelae of COVID-19

Abstract: Coronavirus 2019 (COVID-19) is currently the center of what has become a public health crisis. While the virus is well-known for its trademark effects on respiratory function, neurological damage has been reported to affect a considerable proportion of severe cases. To characterize the neuro-invasive potential of this disease, a contemporary review of COVID-19 and its neurological sequelae was conducted using the limited, but growing, literature that is available. These neurological squeal are based on the man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
79
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(88 citation statements)
references
References 33 publications
0
79
0
9
Order By: Relevance
“…Importantly, the COVID-19 associated dysgeusia may be explained by the viral replication in the solitary tract neurons. It is also suggested that SARS-CoV-2 can disrupt the chemoreceptors by invading the olfactory mucosa to trigger an inflammatory response ( Fiani et al, 2020 ). The COVID-19 associated early anosmia may be a result of the early neuroinvasion, probably through the olfactory bulb as HCoV utilizes retrograde transport to reach the olfactory nerve.…”
Section: Plausible Neurotropic and Neuroinvasive Mechanismsmentioning
confidence: 99%
“…Importantly, the COVID-19 associated dysgeusia may be explained by the viral replication in the solitary tract neurons. It is also suggested that SARS-CoV-2 can disrupt the chemoreceptors by invading the olfactory mucosa to trigger an inflammatory response ( Fiani et al, 2020 ). The COVID-19 associated early anosmia may be a result of the early neuroinvasion, probably through the olfactory bulb as HCoV utilizes retrograde transport to reach the olfactory nerve.…”
Section: Plausible Neurotropic and Neuroinvasive Mechanismsmentioning
confidence: 99%
“…The infection may result in the COronaVIrus Disease 2019 (COVID-19), a severe systemic disease, in which pneumonia is the dominant clinical manifestation, but also other systems might be involved, such as cardiovascular, nephrological and neurological (Bansal, 2020 ; Bose & McCarthy, 2020 ; Fiani, Covarrubias, Desai, Sekhon, & Jarrah, 2020 ; Tadolini et al , 2020 ), leading to the need for hospitalization. Hospitalized COVID-19 patients had to deal with a complex and potentially highly stressful situation: as known from other infectious pandemics, patients have been exposed to several stressors such as isolation, uncertainty about treatment and prognosis, fear of death and of infecting loved ones, and lack of support from relatives (Chua et al , 2003).…”
Section: Introductionmentioning
confidence: 99%
“…COVID 19 has created an unprecedented public health emergency for almost a year since its emergence from Wuhan, China in December 2019 (Novel Coronavirus -China, 2021) . With the alarming rate of infectivity, considerable rate of mortality, and privation of effective treatment as well as an effective vaccine to prevent transmission, has made the disease the biggest health and economic threat of the century (Fiani et al, 2020). Although initially emerged as a respiratory illness, COVID-19 was later established to cause more widespread symptomatology for its affinity to ACE-2 receptors (Carod Artal, 2020).…”
Section: Introductionmentioning
confidence: 99%